Political Dynamics in Indonesia: A Literature Review on the Direction of Democratic Consolidation and Power Polarisation - Sukendar, Sukendar (Indonesian Journal of Social Science Research, 2025)
The 2024 general election marks a new phase in Indonesian politics, as Joko Widodo's two terms in office come to an end. This article aims to evaluate post-Jokowi political dynamics through a literature review approach to issues such as elite configuration, democratic institutionalisation, the role of the military, and the influence of oligarchy in Indonesia's political system. The research findings reveal a paradox between procedural stability and substantive democratic regression. The post-Jokowi transition reveals a contest between continuity and change, with a tendency toward the re-strengthening of oligarchic actors and the centralisation of power. This study contributes to academic understanding of the relationship between power structures, democratic institutions, and the dynamics of political actors in a democracy that has not yet been consolidated.